THE MORPHOMETRY AND SEX RATIO OF Gerris marginatus Say (HETEROPTERA: GERRIDAE) IN TROPICAL AREA - Ni Luh Watiniasih (Environmental Research Center (PPLH) of Udayana University, 2015)
Gerris marginatus is one fresh water insect distributed from temperate to tropicalareas. It can be found in almost every freshwater biotope, making them excellent objects forecological and biogeographic studies. Most recent studies found that this water insect wasone good candidate for examining the effect of fresh water pollution. This species showsmorphometric differences between male and female, but there has no studies examining thismorphometric differences particularly in tropical areas. This study aimed to determine andinvestigate the morphometric differences between male and female and their sex ratio of G.marginatus in one of freshwater body in Bali. Samples were collected from Jangu River atKarangasem Regency on February 2014. Samples were preserved in 70 % awaiting foridentification and further studies. Identification was performed at Animal TaxonomyLaboratory, Biology Department. The results show that there were morphometric differencesbetween male and female of G. marginatus in tropical area. Males were significantly largerof many variable measured compared to females. However, they also exhibit sex ratio biastoward females.